N-Acetylcysteine Attenuates Hyperalgesia in Rats with Diabetic Neuropathic Pain: Role of Oxidative Stress and Inflammatory Mediators and CXCR4 - Sisi Li; Xuying Li; Xiangbin Xie; Xiao Wei; Cong Yu; Chi Wai Cheung; Zhengyuan Xia; Guogang Tian (Journal of Diabetes Research)
Objectives. CXCR4 plays critical roles in the development of diabetic neuropathic pain (DNP) in rats, and its mechanism is unknown. This study was aimed at evaluating the potential therapeutic value of the antioxidant N-acetylcysteine (NAC) against DNP in rats and how CXCR4 participates in the formation of DNP. Methods. Control or streptozotocin- (STZ-) induced diabetic Sprague-Dawley rats received vehicle or NAC for four weeks starting one week after STZ injection. Von Frey and Hargreaves Apparatus were used to analyze the behavioral changes of mechanical allodynia and heat hyperalgesia. CXCR4, p-CXCR4, interleukin- (IL-) 6, and tumor necrosis factor- (TNF-) α in the spinal cord and the prefrontal cortex were detected by western blotting. Plasma IL-6, TNF-α, superoxide dismutase- (SOD-) 1, SOD-2, and lipid peroxidation products malondialdehyde (MDA) and 15-F2t-Isoprostane were detected by ELISA. Results. The values of paw withdrawal threshold (PWT) and paw withdrawal latencies (PWL) were reduced in diabetic rats compared to control rats that were concomitant with significant increases of CXCR4, p-CXCR4, IL-6, and TNF-α protein expressions in the spinal cord and prefrontal cortex. The treatment with NAC decreased the IL-6 and TNF-α protein expression and further increased CXCR4 and p-CXCR4 in the spinal cord and the cortex of diabetic rats that were accompanied with enhancement of PWT and PWL. NAC also significantly attenuated or reverted the increases of plasma IL-6, TNF-α, SOD-1, SOD-2, MDA, and 15-F2t-Isoprostane in diabetic rats. Conclusion. It is concluded that NAC treatment could effectively alleviate DNP and that induction of CXCR4 and p-CXCR4 may represent a mechanism whereby NAC attenuates DNP.